Sustainable Supply Chain Risk Management in Dairy Industry: An Empirical Study in Bangladesh - Nasir, Tasnuba (Curtin University, 2016)
This study investigates the existing dairy supply chain risks in a developing country to find appropriate mitigation strategies to achieve sustainable benefits. . A mixed methods approach is used under positivist paradigm using Quality Function Deployment technique. High probable and high impact risks and mitigation strategies are found and categorised in terms of sustainability dimensions. The findings of the study recommend several policy implications. Future directions for further research are also suggested.